Are teachers' ratings of students' creativity related to students' divergent thinking? A meta-analysis. (September 2019) - Gralewski, Jacek; Karwowski, Maciej
Highlights: The association between teachers' ratings of students' creativity and students' divergent thinking was assessed. The observed link was significant, yet weak. Moderator analysis called for more elaborated measurement of teachers' ratings. Abstract: This article meta-analytically examines the relationship between teachers' ratings of students' creativity and students' creative abilities as measured with divergent thinking tests. Based on 135 correlation coefficients derived from 27 studies, we found a statistically significant, yet weak-to-moderate ( r  = .23) relationship between students' divergent thinking and teachers' ratings of students' creativity. This correlation was stronger when teachers used more elaborate and reliable scales to rate students' creativity than when their ratings were based on single indications of whether a student was more or less creative. We discuss the implications of the obtained results for the practice of creative learning and teaching.